Differente Lernkulturen - regional, national, transnational - Dörner, Olaf (Schriftenreihe der Sektion Erwachsenenbildung der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2016)
In contrast to earlier debates on the subject of "learning cultures", regional, national and transnational perspectives are added today - learning cultures are constituted in different ways at different levels. There is no shortage of contradictions and surprises, so that the development of learning cultures also develops into a complex event. The volume collects selected and peer-reviewed contributions on this topic